Vulneración al derecho de libre acceso al órgano jurisdiccional en la reducción de pensión alimenticia 2019 - Herrera Tello, Julio Cesar (2020)
The present work was developed in the department of La Libertad, Province of Trujillo; where article 565-A of the Civil Procedural Code was studied, based on an analysis and questioning of the theoretical / practical aspect of this provision that affects a constitutional right of the provider when accessing a court. Having as a general objective to determine the violation of access to the court when the reduction of maintenance is requested. All this based on a type of basic research, under the design of grounded, non-experimental theory that included the participation of judges, teachers and lawyers specializing in Civil and Constitutional Law, who contributed to the development of the research with their extensive knowledge objectively, driving the development of it through their work experience and national and international research. Finally, the investigation showed that there is a violation of the right of free access to the court, since the legislator has conditioned and, at the same time, hampered the supporter from exercising his constitutional right regardless of whether the ruling was favorable or no.